A study on design and develop a concurrent problem solvine method in Mould Flow Analysis - Wahizatun Akmar Abd Wahab (School of Manufacturing Engineering, University Malaysia Perlis, 2010)
This paper were discussed a concurrent problem solving method in mold flow analysis that is fully automatic approach of integrated injection molding parameter optimization and simulation to plastic injection molding problems.